Fathers’ Experiences of Negotiating Co-Parenting Arrangements and Family Court - Benjamin Hine; Eilish Mairi Roy; Ching-Yu Huang; Elizabeth Bates (Social Sciences)
Background: this study builds on existing research on fathers’ experiences of family breakdown, separation, and post-separation abuse, exploring the systemic challenges they face in negotiating co-parenting arrangements. Methods: using data from a survey of 141 fathers and interviews with 30 participants, we examined the dynamics of post-separation co-parenting, particularly focusing on how fathers perceive and navigate family court systems. The data were analysed using reflexive thematic analysis to identify key themes. Results: the findings highlighted two primary themes: the difficulties that fathers face in establishing equitable co-parenting arrangements and their negative experiences with family courts, including perceptions of gender bias and systemic inefficiency. Conclusions: the results indicate a need for greater support mechanisms post-separation to facilitate healthier co-parenting relationships and minimise reliance on adversarial court processes. Furthermore, the research underscores the importance of addressing gender stereotypes within family law and social services to ensure more just outcomes for fathers and their children.